2013
DOI: 10.2320/matertrans.m2012363
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Conductive Nano Ink Using 1-Octanethiol Coated Copper Nano Powders in 1-Octanol for Low Temperature Sintering Process

Abstract: A conductive nanoink was prepared using copper nanoparticles (CNPs). In order to prevent the oxidation of CNPs, the particles were coated by 1-octanethiol using Vaporized Self-Assembled Multi-layers (VSAMs) method. The coating of 1-octanethiol onto CNPs was confirmed by transmission electron microscope (TEM) and X-ray photoelectron spectroscopy (XPS). Dispersion stability of CNPs was checked by monitoring its viscosity over 6 weeks. The sheet-type of patterned samples using the fabricated ink was sintered at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Its diffraction pattern in the inset shows that the surface has not been oxidized. Oxidation prevention by 1-Octanethiol has been discussed previously [16,17]. Therefore, it was confirmed that 1-Octanethiol layer was successfully coated on surface of each copper nanoparticle via coating system through TEM analysis.…”
Section: Fabrication and Characterization Of Copper Nanoink With Rgosupporting
confidence: 57%
See 1 more Smart Citation
“…Its diffraction pattern in the inset shows that the surface has not been oxidized. Oxidation prevention by 1-Octanethiol has been discussed previously [16,17]. Therefore, it was confirmed that 1-Octanethiol layer was successfully coated on surface of each copper nanoparticle via coating system through TEM analysis.…”
Section: Fabrication and Characterization Of Copper Nanoink With Rgosupporting
confidence: 57%
“…Sintering was conducted under H 2 gas (500 sccm) at a heating rate of 5 ∘ C/min ( Figure 1) [16]. The line resistivity of the sintered patterns was measured immediately after sintering and monitored for 200 days.…”
Section: Fabrication and Characterization Of Copper Nanoink With Rgomentioning
confidence: 99%
“…Copper nanoparticles were synthesized by polyol method with an average diameter of 100nm by Lee et.al. 35 . Typical experimental procedure includes preparation of copper nanoparticles stabilized in PVP in ethylene glycol solution by polyol method 29 .…”
Section: Polyol Synthesismentioning
confidence: 95%
“…The Cu oxidation was inhibited by the protective layers formed by Cu–S bonding of 1-octanethiol for 35 days [ 81 ]. Her et al prepared 1-octanethiol-protected Cu nanoparticles with an average diameter of 100 nm using the dry coating vaporized self-assembled multilayers (VSAMs) method to prevent the oxidation of Cu nanoparticles [ 82 ]. The thermogravimetry differential thermal analysis (TG/DTA ) curves indicated that 1-octanethiol could be removed at 150 °C, allowing the low-temperature sintering of the Cu nanoparticles.…”
Section: Surface Designs By Surface Protective Layers Against the mentioning
confidence: 99%